Zunyimycin C enhances immunity and improves cognitive impairment and its mechanism - Wang, Xuemei; Li, Zexin; Sun, Rui; Li, Xueli; Guo, Ruirui; Cui, Xiangyi; Liu, Bingxin; Li, Wujuan; Yang, Yi; Huang, Xiaoyu; Qu, Hanlin; Liu, Chen; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
This study aimed to explore the efficacy of zunyimycin C in the immunological enhancement of hypoimmune mice and improvement of cognitive impairment in a mice model of Alzheimer’s disease (AD). Zunyimycin C was administered intranasally to interfere with AD mouse models or gavage to hypoimmune animals. Results of the Morris water maze (MWM) showed that zunyimycin may improve the learning and memory abilities of the AD mice model. The results of differential expression analysis of mRNA levels of inflammatory factors and pathways in brain tissues of the AD mouse model suggested that differential expression was more obvious under Zun-Int L. Western blot revealed that the relative expression of glial fibrillary acidic protein in the brain tissue of the AD mouse model in the Zun-Pre group was significantly higher than that in the other groups, and the difference was statistically significant. The relative expression of interleukin (IL)-6 protein in the brain tissue of mice in the low-dose intervention group was significantly lower than that in the other groups, and the difference was statistically significant. As for hypoimmune animals, short chain fatty acids (SCFAs) assay and intestinal flora assay results showed that zunyimycin C may change intestinal flora diversity and SCFA biosynthesis. The prophylactic administration of zunyimycin C could not inhibit acute neuroinflammation in AD mice. Zunyimycin C may participate in the immune response by activating the Ras-Raf-MEK-ERK signaling pathway to stimulate microglia to produce more inflammatory factors. Zunyimycin C may inhibit autophagy by activating the PI3K-AKT-mTOR signaling pathway, promote cell survival, mediate neuroprotective effects of reactive microglia and reactive astrocytes, and reduce IL-1β in brain tissue and IL-6 secretion, thereby attenuating neuroinflammation in AD mice and achieving the effect of improving learning and memory impairment. Zunyimycin C may play a role in immunological enhancement by changing intestinal flora diversity and SCFAs.